From Hi-Tech to Hi-Touch: A Global Perspective of Design Education and Practice (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue papers comprise classified into four categories: The first category includes three papers that examine the practical application of design theory in different contexts. The second category comprises three papers exploring the role of technology in design education. The third category includes three papers that analyze the intersection of design education and cross-cultural communication. The final category encompasses two papers investigating the application of design education in diverse fields. It offered invaluable insights into the latest pedagogical approaches, technologies, and trends in the field of design education. It provided a rich and nuanced view of the challenges and opportunities faced by design educators today. It was an invaluable resource for researchers, educators, and practitioners in the field of design education.